REVITALISASI KEKUDUSAN DALAM HIDUP PELAYAN KRISTEN - Roy Charly H. P. Sipahutar (Jurnal Teologi Cultivation, 2018)
Abstrak This article attempts to discuss issues of importance in the practical struggle of faith of the church today. Holiness became a major theme in this paper that should also be the key to every Christian Minister. With the socio-historical approach then this article tries to see infull what the Bible says about holiness Holiness is not a status quo that makes stagnate and remain silent, but is a to be lived in the life of every Christian minister. Kata Kunci: Holiness, Christian minister, John Wesley